Play School with Big Sister Hawa (African Knowledges and the History Publication since the 1970s, 1990)
Two educational shows for elementary school children with singing, instrumental music and learning on blackboard and one episode dedicated to the topic of natural conservation (Earth Day 1990).
Keywords: Education; Singing; Dance; Children; Educational Show